2020
DOI: 10.1186/s12885-020-06928-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative SCC-Ag as a predictive marker for the use of adjuvant chemotherapy in cervical squamous cell carcinoma with intermediate-risk factors

Abstract: Background: For cervical cancer patients whose tumors display a combination of intermediate risk factors, postoperative radiation with or without adjuvant chemotherapy is suggested for them. However, who should be administered with adjuvant chemotherapy is unknown. The current study was designed to explore the clinical value of squamous cell carcinoma antigen (SCC-Ag) in guiding the use of adjuvant chemotherapy in cervical cancer patients. Methods: A total of 301 cervical cancer patients were included in the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is present at high levels in 20–60% of patients with early stage cervical cancer (CC), with abnormally high levels also observed in 25% of individuals with adenocarcinoma (ADC) [ 7 ]. Recent studies have established that elevated levels of SCC-Ag is associated with extensive tumor, poor survival of patients treated by CCRT, and radiotherapy resistance [ 71 , 73 ]; and that, preoperative SCC-Ag is equally useful in predicting adjuvant chemotherapy outcome in patients with intermediate-risk factors [ 74 ]. Unfortunately, few studies have evaluated the performance of SCC-Ag assay, either as single biomarker or in combination with other complementary biomarkers; thus, calling for more robust clinical translation studies with larger consecutive cohorts of women participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is present at high levels in 20–60% of patients with early stage cervical cancer (CC), with abnormally high levels also observed in 25% of individuals with adenocarcinoma (ADC) [ 7 ]. Recent studies have established that elevated levels of SCC-Ag is associated with extensive tumor, poor survival of patients treated by CCRT, and radiotherapy resistance [ 71 , 73 ]; and that, preoperative SCC-Ag is equally useful in predicting adjuvant chemotherapy outcome in patients with intermediate-risk factors [ 74 ]. Unfortunately, few studies have evaluated the performance of SCC-Ag assay, either as single biomarker or in combination with other complementary biomarkers; thus, calling for more robust clinical translation studies with larger consecutive cohorts of women participants.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of SCC-Ag is associated with shorter overall survival (OS) and a higher rate of metastasis [3]. Many studies have shown that the SCC-Ag level is an important prognostic factor for cervical SCC, which can guide the development of a more active treatment plan [3,12,13]. In this study, the prognostic value for post-treatment cervical SCC was evaluated using a combination of 18 F-FDG PET/CT whole-body metabolic tumour load and SCC-Ag level.…”
Section: Introductionmentioning
confidence: 99%